Autoimmune hepatitis: trust in transaminases. (23rd April 2014) - Brissos, Joao; Carrusca, Catarina; Correia, Marta; Cabral, José
Abstract : A rational and appropriate evaluation of liver biochemical tests is essential, given the increased number of abnormal laboratory results in asymptomatic patients. Critical judgement allows early diagnosis in the absence of typical clinical signs. Autoimmune hepatitis is a rare disease with high clinical variability. We present a child investigated for unexplained increase in aminotransferases, discovered accidentally 2 months earlier in a standard laboratory panel approach. She was asymptomatic and no physical signs of chronic or acute liver disease were found. Laboratory investigation showed hypergammaglobulinaemia with selective elevation of IgG and a positive anti-liver cytosol type 1. Severe interface hepatitis was found on liver biopsy and treatment was initiated with steroids and azathioprine with good response. This case highlights the importance of trusting in any serum aminotransferase abnormality, even in asymptomatic children and emphasises the value of clinical suspicion and specific immunosuppressive therapy in prognosis.